Kekerasan Seksual: Berkelindan di Antara Norma Hukum dan Agama - Maria Ulfah Anshor (Yayasan Jurnal Perempuan, 2023)
Sexual violence experienced by women with a variety of experiences is at the risk of not being recognized by the public, even by law enforcement officials who are not conscious of a victim’s perspective. This shows that there is a ‘big’ problem related to the public’s perspective on legal norms which makes its implementation conflicting with the constitution which guarantees rights and access to justice for women as citizens. This problem is also supported by an interpretation of religion that is not in favor of victims of sexual violence. This research is carried out to ensure that women who became victims of rape have access to justice in safe abortion services guaranteed by the constitution and religion (Islam). This is the novelty of this research, which is expected to fill in the gaps in a number of previous studies. The research methodology uses a descriptive qualitative approach.